Ad hoc Japonisme: how national identity rhetorics work in Japanese advertising. Issue 4 (4th July 2017) - Minowa, Yuko; Belk, Russell W.
ABSTRACT: This study examines how a variety of national identity rhetorics are formed with the nuanced aestheticization. We focus on visual rhetorics. We use advertisements for traditional, seasonal gifts in post-postwar Japan as the context of inquiry. Two research questions addressed are: (1) how different rhetorics of national identity are formed between the gifts advertised and the audience, focusing more on visual than merely verbal elements, and (2) how visual genealogy – specific cultural and historical references in contemporary images – is used in rhetorical figures. Underpinned by a critical visual analysis, we apply Western and Japanese art canons to a visual social semiotic approach in order to interpret variations in the semantics of national identity. We discuss three types of rhetorics of national identity: rhe-transfiguration, rhe-truculence, and rhe-trepidation. The study suggests that national identity rhetorics activate a "deep subjectivity" resulting from the aestheticized experience reinforced by the nation's consumption ritual.